Coal - Experimental Work in the Degasification of the Pittsburgh Coal Seam by Horizontal and Vertical Drilling - G. R. Spindler; W. N. Poundstone (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
A comprehensive report on extensive experimentation in degasification of the Pittsburgh Coal seam is presented. Detailed accounts of the procedures and results are given for permeability tests, vertical bore hole tests, measurement of gas flow from sealed drainage areas, horizontal rib hole tests, and water infusion tests. The removal of methane gas from coal seams in advance of mining is not a new idea with mining men—much attention has been given to the possibility for many years. In other parts of the world, a principal concern has been in the recovery and utilization of the gas and a number of successful projects have been developed in Europe and elsewhere. In this country, the principal motivation has been related to the safety aspect with some possible side benefits concerning costs and efficiency in mining as secondary objectives. To date, experimental work in this country has been largely or entirely exploratory to determine bed characteristics with respect to the liberation of combustible gases to investigate or establish the possibility of degasification in advance of mining and as an aid in projecting mine ventilation systems to provide for safe, effective and economical handling of combustible gases liberated during mining. With these objectives in mind, the School of Mines and Engineering Experiment Station at West Virginia University, in cooperation with the Christopher Coal Co. of Osage, W. Va., initiated some experimental work in May 1952 and the project has been more or less continuous since that time. The work has been centered entirely in mines of the cooperating company in Monongalia County, W. Va., and Greene County, Pa. LOCATION AND GENERAL CONDITIONS OF THE AREA The principal mining in the area involved is in the Pittsburgh coal seam which lies at the bottom of the Monongahela series of the Pennsylvanian. The Pittsburgh coal in the area is generally uniform in its structure and physical characteristics. The bed thickness averages about 7 to 8 ft and the coal has a characteristic blocky structure as the result of pronounced face cleats and definite, but somewhat less pronounced, butt cleavage. It is a medium volatile coal, averaging about 37 pct, and is marketed principally as a steam fuel and for metallurgical purposes. The Pittsburgh coal outcrops along the Monongahela River and dips gradually, but not uniformly, slightly north of west (about N75°W). The westward extensions of the bed, from the areas contiguous to the Monongahela River which have been heavily mined, constitute the principal reserves and are all well below drainage with the depth of cover increasing with the distance from the river. In general, with deeper cover, it may be expected that methane liberation will be more of a problem in future mining as compared to areas mined previously; therein lies the interest in possible de-gasification in advance of mining. Fig. 1 shows the Pittsburgh coal area in the vicinity of Morgantown in Monongalia County, W. Va., and Greene County, Pa., in which the experimental work discussed is located. Fig. 2 shows the contours on the Pittsburgh coal in the test area. It will be noted that the first two bore holes for the experiments were at the edge of a bench or terrace with considerable change in the gradient in the immediate vicinity of the test holes and that the same general condition applies to later test areas. Mining is intensively mechanized in the area and in the mines involved in the experimental work with corresponding rapid advance of working faces a typical characteristic. In the areas now mined the total methane liberation ranges from moderate to relatively heavy, but the actual face liberation is extremely variable and may range from practically